Sustainable development of territories in the framework of smart initiatives - V., Liubov (Scientific Journal of Bielsko-Biala School of Finance and Law, 2020)
The research based on analysis smart city-initiatives in framework of sustainable development. The main hypothesis is a lack of a comprehensive vision of a smart city slows down the development of the city as a whole. The results of research are developed methodology of community analysis and designed template for competitive passport of the city (community). The competitive passport of the city that developing on bases of proposed methodology will allow to reveal explicit and implicit competitive advantages of the territory, to choose the most needed at this stage of smart-technology, to develop an up-to-date strategy with specific (measurable and achievable) goals. Thereby using the concept of smart cities allows cities, regardless of their size, to achieve economic development, attract investors, and mobilize local people and create new jobs. The smart platform allows share data between all participants and stakeholders, this improves efficiency and stimulate changes.